Konsep Pemerolehan Bahasa Arab sebagai Bahasa Kedua dan Relevansinya bagi Pembelajaran di Madrasah - Dimas Putra Hidayat; Hermalia Putri Cahya; Zahro’ Ummi Nashiifah; M. Yunus Abu Bakar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
. This research examines the application of approaches to recognize students’ second language learning capacities in Arabic instruction at Madrasah Aliyah Al-Hikmah Surabaya. Utilizing a qualitative descriptive method, data collection involved participant observation, intensive interviews with educators and learners, and review of documents such as portfolios and diagnostic exam outcomes. Results indicate educators employ varied recognition methods, including preliminary diagnostic evaluations grouping learner talent into high (35%), moderate (45%), and low (20%) levels, monitoring of interaction dynamics in classroom bi’ah lughawiyah settings, and genuine portfolio assessments evaluating listening, speaking, reading, and writing abilities with robust reliability (α=0.82). These methods support flexible curriculum adjustments, customization of instruction techniques like muhadatsah for talented learners and phonetic corrective sessions to counter L1 disruption, coupled with immersive tools like YouTube boosting listening progress scores by 35%. Successful deployment markedly enhances Arabic mastery, lowers dropout figures by 22%, and reinforces Krashen’s principles along with metacognitive tactics. The conclusion stresses the need for nationwide talent screening in madrasahs to maximize L2 attainment. Keywords: talent recognition, Arabic instruction, madrasah, genuine assessment, bi’ah lughawiyah.